Essays on material flow management during disasters : material convergence and panic buying - Martin, J. Lemuel (Nanyang Technological University, 2021)
During disasters, the complexity of material flow management can overwhelm unprepared entities, from retailers to relief providers. This dissertation focuses on two disaster-related material flow phenomena with prominent behavioral components: material convergence and panic buying.